1964
DOI: 10.1126/science.143.3606.594
|View full text |Cite
|
Sign up to set email alerts
|

Vision and Touch: An Experimentally Created Conflict between the Two Senses

Abstract: Observers were presented with an object whose visual shape, because of optical distortion, differed considerably from its tactual shape. After simultaneously grasping and viewing the object, the observers were required to indicate their impression of it by drawing it or by matching another object to it. The results reveal that vision is strongly dominant, often without the observer's being aware of a conflict.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
371
10
3

Year Published

1965
1965
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 622 publications
(408 citation statements)
references
References 3 publications
24
371
10
3
Order By: Relevance
“…Research on intersensory interactions of haptic inputs with other modalities has predominately focused on how vision is combined with touch, although haptic/ auditory interactions have also been studied (e.g., Jousmäki & Hari, 1998;Rock & Victor, 1964;Spence, Nicholls, & Driver, 2001). In keeping with modality specializations outlined above, the relative weighting of vision in relation to touch is greater when geometric properties are being judged than when material properties are tested.…”
Section: Other Significant Issues Vision-touch Interactionsmentioning
confidence: 99%
“…Research on intersensory interactions of haptic inputs with other modalities has predominately focused on how vision is combined with touch, although haptic/ auditory interactions have also been studied (e.g., Jousmäki & Hari, 1998;Rock & Victor, 1964;Spence, Nicholls, & Driver, 2001). In keeping with modality specializations outlined above, the relative weighting of vision in relation to touch is greater when geometric properties are being judged than when material properties are tested.…”
Section: Other Significant Issues Vision-touch Interactionsmentioning
confidence: 99%
“…Over many years of research, it has been found that perceptual dominance between vision and touch can depend on the nature of the task that observers have to perform. For instance, when required to judge object size, people seem to rely much more on vision than touch (e.g., Rock & Victor, 1964). However, in tasks requiring texture judgments (e.g., smoothness, roughness), people can rely equally on one or the other sense (Heller, 1982;Jones & O'Neil, 1985;Lederman & Abbott, 1981), or touch can dominate over vision (Lederman, Thorne, & Jones, 1986).…”
mentioning
confidence: 99%
“…In this way it is possible to dissect the influence of each input, by determining how closely the percept follows one input relative to another. For example, Rock and Victor (1964) used a distorting lens to introduce a discrepancy between the seen and felt shape of objects. Their participants reported shapes more consistent with the visual than with the haptic stimulus.…”
Section: Introductionmentioning
confidence: 99%